Pengaruh Literasi Keuangan, Pengelolaan Uang Saku dan Motivasi Belajar terhadap Produktivitas Keuangan Siswa: The Influence of Financial Literacy, Pocket Money Management and Learning Motivation on Student Financial Productivity - Melani Teta Anggraeni; Melany Ade Putri; Nabila Dwi Aulia; Shafira Renata Anandita; Sheva Nadinant Putri; Rudianto Rudianto (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
The role of financial productivity in students is crucial for developing good financial habits during their academic years. This research focuses on analyzing the role of financial literacy, pocket money management, and learning motivation impact students' financial productivity. Despite this, empirical evidence shows that students often struggle with managing their finances effectively, mainly due to inadequate financial literacy, poor pocket money management, and inconsistent learning motivation. Quantitive methods are employed in this study to involving 160 respondents as questionnaire participants, with data processed via IBM SPSS version 27. Quality assessment of the data confirms that each survey item meets the standarts of validity and reliability, as the correlation values for each indicator surpass the critical value of 0.155 and the internal consistency of each variable surpasses 0.600. T-test findings indicate that financial literacy exerts a notable affects students' financial productivity significant at the 0.05 level, with p = 0.024. Additionally, pocket money management and learning motivation significantly influence financial productivity, each having a yielding p = 0.001. While, the F-test demonstrates that financial literacy, pocket money management, and learning motivation collectively impact students’ financial productivity, with a significance level of 0.001. These results underscore the importance of robust financial skills, efficient pocket money management, and strong learning motivation as key factors in boosting students' financial productivity